Etnične manjšine v primežu avtohtonosti, identitete in integracije - Samardžija, Miro (Socialno delo, 2011)
The article deals with autochtonism which as a conception emerged in the Slovenia Constitution at the end of the 80s in the article 64 and consolidated position of the Italian and Hungarian national minorities in Slovenia. The article aims to demostrate that such usage of the autochthonism - as a constitutional notion designed for minority rights protection - is, on the one hand, unnecessary and, on the other hand, even discriminatory against those national minorities, which are still excluded from Slovenia's legal order and from the policies of recognising etnic minorities.Primarily we are talking about constitutionally unrecognised national minorities from the regions of ex-Yugoslavia. Furthermore, the article deals with two key, and at the same time, quite problematic notions significant for the national minority issues: ethnic identity and integration.
Keywords: etnične manjšine; avtohtonost; integracija; identiteta